Systemic approach to the new production research challenges - Chiu, Anthony Shun Fung (Animo Repository, 2020)
This virtual special issue highlights emerging production research challenges alongside a systemic approach in forms of novel contributions in literature review, thematic analyses, and methodological advances. The selected articles provide insights on how new production research challenges bring about opportunities for growth in sub-fields of supply chain networks, new product development, environmental and economically viable issues, service value chain, and machine learning among others. In this article, an overview of key organizational characteristics as well as significant theoretical ideas and practical applications to production research issues are presented. Future directions in the production research domain are also provided. © 2019